Reconstructing Rape Sanctions in Indonesia: Towards an Integrated Value Framework - Ishaq, Ishaq; Ishaq, Fadhli Muhaimin; bin Ahmad Nadzri, Amirulhakim (Faculty of Law, Jambi University, 2025)
The research examines the criminal sanctions against rape offences in Indonesia and evaluates their consistency with the principles of justice within the framework of Indonesian values. The research revealed that the Indonesian criminal laws have not provided maximum protection to rape victims and have not reflected the value of substantive justice due to the relatively lenient criminal sanctions and the absence of moral and religious aspects in their formulation. As a result, the protection of the victims is normatively abandoned. While previous studies have failed in formulating a unified model of justice for rape victims, the present research addresses this gap by synthesizing Indonesia’s fundamental normative frameworks, representing the living law in Indonesia. Arguing that living laws can operate more effectively and foster compliance within society, this research proposes an integrative and equitable model of punishment that combines modern penal principles with Islamic legal values that serve as the philosophical, moral, and sociological foundations for reforming national criminal law, particularly in efforts to address such sexual punishment as rape. The theoretical contribution of this research is to provide a new perspective regarding the penalization of rape by encouraging the principles of Maqāṣid al-Sharī’ah as an alternative normative approach, combined with Pancasila, modern perspective. Moreover, it provides practical recommendations for revising the formulation of rape sanctions in the Indonesian Criminal Code to better reflect justice for victims and to have a strong deterrent effect on perpetrators, while granting rights for the victims.